2017
DOI: 10.21037/atm.2017.01.64
|View full text |Cite
|
Sign up to set email alerts
|

The Ross procedure: time for a hard look at current practices and a reexamination of the guidelines

Abstract: The ideal aortic valve substitute for young adults requiring aortic valve replacement (AVR) remains elusive. Young and middle-aged patients have a longer anticipated life expectancy and a higher level of physical activity than their elderly counterparts. In recent years, there has been a growing focus on long-term outcomes following AVR in this specific patient population. These studies highlight the direct impact of the choice of prosthesis on long-term survival, quality of life and rates of valve-related com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…There is now clinical evidence that the Ross procedure in the young and middle-aged patients is associated with excellent outcome. [4][5][6][7][8][9][10] Long-term results are growing for the freestanding or inclusion technique [11][12][13] but are scarce for the original subcoronary technique. Furthermore, there is a lack of a practical VPC for comparison between different techniques and substitutes.…”
Section: Perspectivementioning
confidence: 99%
“…There is now clinical evidence that the Ross procedure in the young and middle-aged patients is associated with excellent outcome. [4][5][6][7][8][9][10] Long-term results are growing for the freestanding or inclusion technique [11][12][13] but are scarce for the original subcoronary technique. Furthermore, there is a lack of a practical VPC for comparison between different techniques and substitutes.…”
Section: Perspectivementioning
confidence: 99%
“…These results come at a time when the Ross operation is under much scrutiny, with several new studies reporting excellent long-term outcomes with this technique, achieving survival comparable with that of the general population 6 7. Several authors have suggested that the current guidelines regarding AVR in the young should be reconsidered with these new data in mind 33 34…”
Section: Discussionmentioning
confidence: 99%
“…The estimated cost of heart valve disease in the United States is 23.4 billion USD per year 96 . Bioengineering can address these issues with the fabrication of biologically compatible and mechanically functional heart valves, at potentially much lower cost 98‐100 …”
Section: Progress In Cardiovascular Bioprintingmentioning
confidence: 99%